Gene and Blood Analysis Reveal That Transfer from Brackish Water to Freshwater Is More Stressful to the Silverside Odontesthes humensis - Silveira, Tony L. R.; Martins, Gabriel B.; Domingues, William B.; Remião, Mariana H.; Barreto, Bruna F.; Lessa, Ingrid M.; Santos, Lucas; Pinhal, Danillo; Dellagostin, Odir A.; Seixas, Fabiana K.; Collares, Tiago; Robaldo, Ricardo B.; et al. (Frontiers in Genetics, 2018)
Silversides are fish that inhabit marine coastal waters, coastal lagoons and estuarine regions in southern South America. The freshwater silversides have the ability to tolerate salinity variations. Odontesthes humensis have similar habitats and biological characteristics of congeneric O. bonariensis, the most studied silverside species and with great economic importance. Studies revealed that O. bonariensis is not fully adapted to freshwater, despite inhabiting hyposmotic environments in nature. However, there is little information about stressful environments for cultivation of silverside O. humensis. Thus, the aim of this study was to evaluate the stress and osmoregulation responses triggered by the osmotic transfers on silverside O. humensis. Silversides were acclimated to freshwater (FW, 0 ppt) and to brackish water (BW, 10 ppt) and then they were exposed to opposite salinity treatment. Silverside gills and blood were sampled on pre-transfer (D0) and 1, 7, and 15 days (D1, D7, and D15) after changes in environmental salinity. The expression levels of genes atp1a3a, slc12a2b, kcnh1, and hspa1a were determined by qRT-PCR for evaluation of osmoregulatory and stress responses. Furthermore, glycemia, hematocrit, and osmolality were also evaluated. The expression of atp1a3a was up- and down-regulated at D1 after the FW-BW and BW-FW transfers, respectively. Slc12a2b was up-regulated after FW-BW transfer. Similarly, kcnh1 and hspa1a were up-regulated at D1 after the BW-FW transfer. O. humensis blood osmolality decreased after the exposure to FW. It remained stable after exposure to BW, indicating an efficient hyposmoregulation. The glycemia had a peak at D1 after BW-FW transfer. No changes were observed in hematocrit. The return to the pre-transfer levels at D7 after the significant increases in responses of almost all evaluated molecular and blood parameters indicated that this period is enough for acclimation to the experimental conditions. In conclusion, our results suggest that BW-FW transfer is more stressful to O. humensis than FW-BW transfer and the physiology of O. humensis is only partially adapted to FW.